KNOWLEDGE LEVEL REGARDING ANEMIA AMONG STUDENTS OF THE FACULTY OF HEALTH SCIENCES, UNIVERSITAS NAHDLATUL ULAMA SUMATERA UTARA - Nurul Amalia Sofyan; Aryeni Aryeni; M Zaidun Sofyan (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2026)
Background: Anemia is a global health problem with a high prevalence and is commonly experienced by adolescents. As prospective healthcare workers, students in the Faculty of Health Sciences are expected to have a sound knowledge of anemia as a basis for promotive and preventive efforts in the community. Purpose: This study aims to determine the level of knowledge of students at the Faculty of Health Sciences Universitas Nahdlatul Ulama Sumatera Utara about anemia. Methods: This study was a quantitative-descriptive study with a cross-sectional design. It involved 69 university students selected using a total sampling technique. Data collection used a validated 25-question questionnaire with